Automated modelling assistance by integrating heterogeneous information sources. (September 2018) - Ángel, Mora Segura; de Lara, Juan; Neubauer, Patrick; Wimmer, Manuel
Highlights: We propose an approach to provide modelling and meta-modelling assistance. Extremo gathers heterogeneous information sources in various technological spaces. The system provides extensible facilities for querying and constraint evaluation. Extremo has been validated in the context of two domains showing positive results. Abstract: Model-Driven Engineering (MDE) uses models as its main assets in the software development process. The structure of a model is described through a meta-model. Even though modelling and meta-modelling are recurrent activities in MDE and a vast amount of MDE tools exist nowadays, they are tasks typically performed in an unassisted way. Usually, these tools cannot extract useful knowledge available in heterogeneous information sources like XML, RDF, CSV or other models and meta-models. We propose an approach to provide modelling and meta-modelling assistance. The approach gathers heterogeneous information sources in various technological spaces, and represents them uniformly in a common data model. This enables their uniform querying, by means of an extensible mechanism, which can make use of services, e.g., for synonym search and word sense analysis. The query results can then be easily incorporated into the (meta-)model being built. The approach has been realized in theExtremo tool, developed as an Eclipse plugin. Extremo has been validated in the context of two domains – production systems and process modelling – taking into account a large and complex industrial standard for classification and product description. Further validation results indicate that the integration ofExtremo in various modelling environments can be achieved with low effort, and that the tool is able to handle information from most existing technological spaces.